2021
DOI: 10.1213/ane.0000000000005375
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Changes via the Lung Recruitment Maneuver Can Predict Fluid Responsiveness in Stroke Volume and Arterial Pressure During One-Lung Ventilation

Abstract: BACKGROUND: We aimed to evaluate the ability of lung recruitment maneuver–induced hemodynamic changes to predict fluid responsiveness in patients undergoing lung-protective ventilation during one-lung ventilation (OLV). METHODS: Thirty patients undergoing thoracic surgery with OLV (tidal volume: 6 mL/kg of ideal body weight and positive end-expiratory pressure: 5 cm H2O) were enrolled. The study protocol began 30 minutes after starting OLV. Simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 28 publications
1
33
2
Order By: Relevance
“…Third, the duration of hemodynamic stability of 1 min might be short. However, we decided the definition referred to the previous studies assessing fluid responsiveness [ 19 , 20 ]. Additionally, as shown in Table 2 , HR and MAP at T0, T1 and T3 were quite similar.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, the duration of hemodynamic stability of 1 min might be short. However, we decided the definition referred to the previous studies assessing fluid responsiveness [ 19 , 20 ]. Additionally, as shown in Table 2 , HR and MAP at T0, T1 and T3 were quite similar.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, we administered 250 mL of HES solely to confirm fluid responsiveness, and do not recommend the continuous administration of HES during surgery. The administration of HES (250 mL) are frequently used in previous studies assessing fluid responsiveness, [ 19 , 44 ] and we consider that there may be few adverse effects induced by this infusion. Despite these limitations, the present study showed a new approach for assessing hemodynamic response after volume expansion in prone position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydroxyethyl starch (HES) was adopted for the fluid responsiveness test in each study, at a dose of 7–10 mL/kg in six studies ( 5 , 13 - 17 ), a dose of 500 mL in two studies ( 6 , 19 ), and a dose of 250 mL in one study ( 16 ). The standards of fluid responsiveness were as follows: Δ[stroke volume index (SVI)] was used in five studies [≥10% in one study ( 18 ), ≥15% in two studies ( 13 , 17 ), >25% in two studies ( 6 , 15 )], ΔCI was used in three studies [≥10% in one study ( 11 ), >15% in two studies ( 14 , 19 )], and ΔSV ≥10% was used in one study ( 16 ). The characteristics of the individual studies are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Recruitment manoeuvres, in the operating theatre or during acute respiratory distress syndrome, change cardiac loading conditions, and in particular, decrease cardiac preload. The decrease in stroke volume during a recruitment manoeuvre (application of continuous positive airway pressure of 30 cm H 2 O for 30 s [ 86 , 87 ], or of 25 cmH 2 O for 25 s [ 88 ]) predicted the response to a subsequent bolus of fluid in surgical patients during anaesthesia [ 86 , 88 ] and during one-lung ventilation [ 87 ]. Interestingly, changes in the plethysmographic perfusion index were tested under the same conditions but had less diagnostic value [ 89 ].…”
Section: Other Testsmentioning
confidence: 99%